Alterations in growth performance and stress responses in juvenile rockfish, Sebastes schlegelii, exposed to dietary chromium with varying levels of dietary ascorbic acid supplementation. (December 2017) - Kim, Jun-Hwan; Park, Hee-Ju; Kang, Ju-Chan
Abstract: Juvenile rockfish Sebastes schlegelii (mean length 10.8 ± 1.4 cm, and mean weight 31.7 ± 3.6 g) were exposed for 4 weeks to different levels of dietary chromium (Cr 6+ ) at 0, 120, and 240 mg/L and ascorbic acid (AsA) at 100, 200, and 400 mg/L. Growth performance of S. schlegelii was significantly decreased due to dietary Cr exposure, whereas lysozyme activity was notably increased. Exposure to dietary Cr resulted in substantial accumulation of Cr in the blood. Levels of two stress indicators, plasma cortisol and heat shock protein 70, of S. schlegelii were increased due to dietary Cr exposure. The results indicated that dietary Cr exposure affected growth performance, lysozyme activity, and stress responses of S. schlegelii, and high levels of AsA supplementation significantly attenuated dietary Cr-induced toxicity. Highlights: Dietary chromium exposure induced a significant growth inhibition f Sebastes schlegelii. Stress indicators of S. schlegelii were considerably increased by dietary chromium exposure. High levels of AsA supplementation were effective to alleviate chromium toxicity.